Kemampuan Metakognitif, Lingkungan Dan Motivasi Belajar Meningkatkan Prestasi Akademik Mahasiswa Poltekkes Bhakti Mulia (Metacognitive Competence, Environment, And Learning Motivation Increase Students’ Academic Achievement Of Bhakti Mulia Health Polyte - Tutik Yuliyanti (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2015)
Abstract: Academic achievement is the important indicator of students’ success in learning. Knowledge and metacognitive regulation, conducive learning environment, and students’ learning motivation are the determination factors in achieving students’ academic achievement. This is an analytic observational quantitative research with cross sectional approach. The sample of this research was 60 student of DIII nursing, the sample was taken by using Stratified Random Sampling and Quota Sampling. The independent variables consisted of metacognitive competence, environment, and learning motivation; meanwhile, the dependent variable was academic achievement. The data analysis used in this research was double linear regression. 1) Every increase of 1 metacognitive competence score increases academic achievement score 0.01 (0.01, b <: 95% CI, 0.01 – 0.01 <; p < 0.001). 2) Each increased 1 score learning environment enhancing academic achievement score 0.01 (0.01, b < 95% CI 0.01-0.01 <; p < 0.001). 3) every 1 score motivation to learn increases academic achievement score 0.01 (0.01, b < 95% CI 0.01-0.10 <; p < 0.001). There is positive influence and significance statistically between metacognitive competence, environment, and learning motivation toward student academic achievement.Key words: metacognitive competence, learning environment, learning motivation, and academic achievement Abstrak: Prestasi akademik merupakan indikator keberhasilan mahasiswa dalam pembelajaran. Kemampuan metakognitif yang bervariasi, lingkungan belajar yang kondusif dan perbedaan motivasi belajar mahasiswa merupakan faktor yang menentukan prestasi akademik. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh kemampuan metakognitif, lingkungan belajar dan motivasi belajar meningkatkan prestasi akademik mahasiswa. Penelitian ini menggunakan jenis penelitian kuantitatif analitik observasional dengan pendekatan cross sectional. Sampel yang digunakan 60 mahasiswa Progam Studi D III Keperawatan dengan teknik: stratified random sampling dan quota sampling. Variabel Independent kemampuan metakognitif, lingkungan belajar dan motivasi belajar. Variabel dependent: prestasi akademik. Data dianalisis dengan analisis regresi linier ganda. 1) Setiap peningkatan 1 skor kemampuan metakognitif meningkatkan 0.01 skor prestasi akademik (b < 0.01, CI : 95%, <0.01-0.01; p < 0.001). 2) Setiap peningkatan 1 skor lingkungan belajar meningkatkan 0.01 skor prestasi akademik (b < 0.01, CI 95% < 0.01-0.01; p < 0.001). 3) Setiap 1 skor motivasi belajar meningkatkan 0.01skor prestasi akademik (b < 0.01, CI 95% <0.01-0.10; p < 0.001). Ada pengaruh positif dan secara statistik signifikan kemampuan metakognitif, lingkungan belajar dan motivasi belajar dapat meningkatkan prestasi akademikKata Kunci : metakognitif, lingkungan belajar, motivasi belajar, prestasi akademik